Studi Tentang Peran Sakti Peksos Dalam Penanganan Anak Berhadapan Hukum (ABH) Dan Rehabilitasi Sosial (Dinas Sosial Kab. Sleman, Yogyakarta) - Yuniyasari Yuniyasari; Zulkipli Lessy (KOLONI, 2024)
This study aims to explore the role of social workers in dealing with children who are in conflict with the law. identify challenges in the social rehabilitation process for children in conflict with the law. To achieve the research objectives, researchers use qualitative methods descriptive approach used. Data was collected from interviews conducted at the Sleman Regency Social Office office. This result proves that the important role of Sakti Peksos in the field as a mediator, advocate, accompanying ABH children from beginning to end. Preparing the community so as not to bring up the past, collaboration with various agencies and the community. Monitoring and evaluation of the rehabilitation process to assess the effectiveness of the rehabilitation program. Therefore, the role of Sakti Peksos with its human resources, the social workers in the Sleman Regency Social Office play a good role in providing child protection to create a sense of security for the community